Periapical Actinomycosis of the Mandible in Diabetic Patient: Comprehensive Case Report and Literature Review - Rocha, Camila Lopes; Alotaibi, Fawaz; Kim, David; Earnest, Laura; Neeley, Emily; Hyppolito, João Octávio Pompeu (Brazilian Journal of Case Reports, 2025)
Periapical actinomycosis is an uncommon infection that may lead to osteomyelitis, especially in immunocompromised individuals like those with uncontrolled diabetes mellitus. This case involves a 22-year-old male with type 1 diabetes who presented with recurrent dental abscesses, pain, and tooth mobility. Imaging revealed extensive periapical lesions in the anterior mandible. Biopsy identified Actinomyces spp., MRSA, and Streptococcus viridans. Due to severe bone destruction, the patient underwent full-mouth extractions, marginal mandibulectomy, and mandibular reconstruction using a microvascular iliac crest flap. A postoperative mandibular fracture necessitated further resection and reconstruction with a custom titanium plate. Vestibuloplasty with a split-thickness skin graft improved soft tissue adaptation, and two implants were placed in the parasymphysis region to support an overdenture. The aggressive infection, worsened by diabetes, required a multidisciplinary approach. The iliac crest flap offered structural support and enabled early prosthetic rehabilitation. This case highlights the need for early diagnosis and integrated treatment to achieve functional and aesthetic success.